Concurrent treatment of raw and aerated swine wastewater using an electrotrophic denitrification system. (February 2021) - Prokhorova, Anna; Kainuma, Mami; Hiyane, Rie; Boerner, Susan; Goryanin, Igor
Graphical abstract: Highlights: Raw and aerated swine wastewater were co-treated using a bioelectrochemical system. Biocathodic denitrification was optimized for stable long-term operation. Anion exchange membrane showed better performance than cation exchange membrane. With cathode poised at −0.6 V (Ag/AgCl) fastest nitrate removal was performed. Autotrophic denitrifying bacteria were highly enriched on cathodes. Abstract: Enhanced nitrate removal in the cathode chamber of bioelectrochemical systems (BES) using aerated swine wastewater under high nitrate levels and low organic carbon was investigated in this study, focusing on the relationship between nitrogen and bacterial communities involved in denitrification pathways. BESs with the anion exchange membrane (AEM) under cathodic applied potentials of −0.6 V vs. AgCl/AgCl reference electrode showed a removal rate of 99 ± 2 mg L −1 d −1 . Moreover, organic compounds from the untreated full-strength wastewater were simultaneously eliminated in the anode chamber with a removal rate of 0.46 g COD L −1 d −1 with achieved efficiency of 61.4 ± 0.5% from an initial concentration of around 5 g of COD L −1, measured over the course of 7 days. The highest microbial diversity was detected in BESs under potentials of −0.6 V, which include autotrophic denitrifiers such as Syderoxidans, Gallionela and Thiobacillus .